Advancing PROMIS''s methodology: results of the Third Patient-Reported Outcomes Measurement Information System (PROMIS®) Psychometric Summit. (December 2011) - Carle, Adam C; Cella, David; Cai, Li; Choi, Seung W; Crane, Paul K; Curtis, S McKay; Gruhl, Jonathan; Lai, Jin-Shei; Mukherjee, Shubhabrata; Reise, Steven P; Teresi, Jeanne A; Thissen, David; et al.
In 2002, the NIH launched the 'Roadmap for Medical Research''. The Patient-Reported Outcomes Measurement Information System (PROMIS ® ) is one of the Roadmap''s key aspects. To create the next generation of patient-reported outcome measures, PROMIS utilizes item response theory (IRT) and computerized adaptive testing. In 2009, the NIH funded the second wave of PROMIS studies (PROMIS II). PROMIS II studies continue PROMIS''s agenda, but also include new features, including longitudinal analyses and more sociodemographically diverse samples. PROMIS II also includes increased emphasis on pediatric populations and evaluation of PROMIS item banks for clinical research and population science. These aspects bring new psychometric challenges. To address this, investigators associated with PROMIS gathered at the Third Psychometric Summit in September 2010 to identify, describe and discuss pressing psychometric issues and new developments in the field, as well as make analytic recommendations for PROMIS. The summit addressed five general themes: linking, differential item functioning, dimensionality, IRT models for longitudinal applications and new IRT software. In this article, we review the discussions and presentations that occurred at the Third PROMIS Psychometric Summit.